Eficiência relativa e eficiência dinâmica dos recursos das universidades federais no contexto da Emenda Constitucional 95/2016 - Napoleão Neto, João Juarez (2021)
The concept of efficiency is related to the optimal combination of resource consumption and product generation. Within the scope of the Brazilian Public Administration, efficiency has become a legal duty, by virtue of the constitutional principle, contemplated in art. 37 of the Federal Constitution (CF) in force. In this sense, efficiency is even more relevant in the context of the fiscal crisis that broke out in 2015, when Constitutional Amendment (EC) no. 95/2016, known as the Law on the Ceiling of Public Spending. Under this focus, the objective of the present study was to analyze the relative efficiency of public resources for academic management within the scope of the Brazilian Federal Institutions of Higher Education (IFES), in the context of the Ceiling Law. For this, this descriptive, quantitative and documentary study made use of the data envelopment analysis, and of the Malmquist Index, both with orientation to outputs and, considering variable returns of scale. As factors of the analysis, data were collected from the IFES Management Reports and the RUF ranking of 58 Brazilian federal universities, from 2016 to 2018. The results revealed that, in 2017, the first year of validity of the EC, there was an increase in the score efficiency, as well as the number of efficient DMUs. In 2018, the average score fell, however, at a level higher than the average observed in 2016. Four universities were efficient in all exercises in the six dimensions analyzed: UFMG, UFPA, UFAM and UFAC and, among them, the first two are discarded as the main benchmarks in the triennium. The greatest potentials for improvement were the RUF score and the number of professors, in outputs and inputs, respectively. UFT was the DMU that presented the greatest gains in productive efficiency in the context of EC 95/2016 and UNIFESSPA presented the greatest losses. In addition, it was found in the analysis of the three-year conglomerate, that old universities with a higher degree of focus for postgraduate studies (PG) had averages in the three years higher than new universities and with a lower degree of focus for PG and the region North had the highest efficiency average, while South, the lowest average in the same period.